Analysis of Mg-based spinels MgGd2X4 (X = S, Se) for spintronic and thermoelectric device applications: Ab-initio calculations. (October 2022) - Noor, N.A.; Majeed, M. Arslan; Khan, M. Aslam; Niaz, Shanawer; Iqbal, M. Waqas; Abbas, Taswar; Dahshan, A.
Abstract: The spin-dependent magnetic, thermoelectric, and electronic characteristics of Mg-based spinels MgGd2 X4 (X = S, Se) are investigated using density functional theory (DFT) calculations. The modified Perdew-Burke-Ernzerhof generalized gradient approximation (PBEsol-GGA) is utilized to compute the structural and elastic characteristics. In addition, the magnetic, thermoelectric, and electronic characteristics are explored employing the modified-Becke and Johnson (mBJ) potential. After the energy difference calculations among the ferromagnetic (FM) and nonmagnetic (NM) phases, the stability of the structures is confirmed in the FM phase. Further, thermodynamic stability is determined by calculating formation energies and phonon dispersion spectra. The Charpin method is used to analyze elastic characteristics in detail. The total magnetic moments are produced by 2p-states of chalcogenides and f-states of Gd atoms, which result in substantial hybridization at the Fermi level. Finally, electronic-thermal coefficients, such as the power factor, Seebeck coefficient, and thermal and electrical conductivity, are investigated, concluding that investigated spinels can be used in thermoelectric devices.